The Analysis Of Dental Health Knowledge With Dental Care Behavior Of School Age In SDN Rejoso I - Winarsih; Wardani, Ratna; Budi Susanto, Setyo (Journal of Global Research in Public Health, 2019)
Dental health problems are influenced by many factors. One of the causes of oral and dental problems in the community is behavioral factors or attitudes to neglect tooth and mouth cleansing.This study aims to analyze the Effect of Knowledge Level on Health care with Behavioral Dental Care of School-aged Children at SDN Rejoso I. This research method using quantitative method with crossectional research design. The population of this study are students of class IV and V in SDN Rejoso I as many as 60 respondents with stratified random sampling technique with the number of sample class IV 29 respondents and class V 31 Respondents. Independent variables of this research is the level of knowledge of dental health while the dependent variable is dental care behavior. The instrument used is a questionnaire. Stastistic test of this research using Ordinal Regression. The results of this study indicate that from a total of 60 respondents most of the respondents knowing that knowledge as much as the respondents (50%). While behavior of dental care showing enough behavior that is as much as respondent (55%). Based on data analysis using Ordinal Reqdition of Health Level of Teeth with Behavior of Dental Care of School Age Children at SDN Rejoso I, obtained sig value: 0,005. Result of this research indicate that level of dental knowledge enough and less impact 8 times from dental treatment behavior so there is influence between Level of Dental Health Knowledge with Child Care Behavior Dental Age children at SDN Rejoso I. Behavior arises according to one’s awareness, knowledge, and attitudes. So a person is able to perform an action that is considered good or wrong according to the stimulus they receive.